Кореферентные структуры, используемые для представления экономических субъектов в медийном дискурсе - Ключенович, Сергей (Linguistik Online, 2021)
The subject of study in the article is the discourse specifics of representation of economic entities in German newspaper and magazine texts of the last two decades. The purpose of the analysis is to elucidate the factors that stimulate univerbation in connection with the generation and textual integration of co-referential structures different in genesis, structural properties, semantic characteristics and stylistic potential.The study, conducted on the basis of a functional-communicative approach to language, relies on methods and results of studies on text linguistics considering text as a whole structural-semantic unit.Conclusions. 1) Mentioning of a company name is accompanied by integration of the univerb indicating the relevant industry into the text. Along with a two-member chain of co-referential nominations, a three-member chain is also possible (the location of a company is mentioned). 2) Co-referential pairs of the type “company name ‒ collective designation of employees according to headquarters location” (Siemens ‒ Münchener) are characteristic, which demonstrates the lability of univerb toponym semantics. 3) The integration of a proper name into the text requires the usage of characterizing common nouns in order to prepare the reader for the perception of unique names, which is a factor motivating univerbation. 4) Synthetic compounds of the nomina agentis type (Autobauer, Stromversorger) are widely used to describe the kind of activity of an enterprise. In such cases a lexeme with the expected semantics is eliminated (Unternehmen ‘company’, Konzern ‘concern’ etc.). The reduction of the base lexeme of a compound as well as representation of the verb lexeme in the form of nomen agentis has an impact on the semantics and stylistics of the univerb.The results of the study can be used both in research activities on problems of word-formation, semantics and in the training of business translators.